Application of Genetic Algorithm in Intelligent Examination Paper Composition - Yan Yan; Dali Yin (Institute of Advanced Engineering and Science, 2014)
With the development of computer technology and artificial intelligence, the research into examination paper composition receives more and more concern, and the artificial composition of examination paper based on the genetic algorithm gradually demonstrates its superiority. However, due to the complexity of the restraints of paper composition, it has many shortcomings. This paper focuses on the application of the genetic algorithm in paper composition, and proposes an improved tactic of arithmetic crossing, which enlarges the searching space of algorithm to a considerable extent, avoiding the defects of the slow convergence of the simple genetic algorithm and regional convergence so that the efficiency and quality of paper composition are raised. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4888